Pelatihan Tata Bahasa Inggris Dasar Secara Daring Sebagai Upaya Peningkatan Kualitas SDM Pada Siswa SMP N 10 Tambun Selatan - Wahyu Budi; Muhamad Ekhsan (JPM: Jurnal Pengabdian Masyarakat, 2020)
English is one of the most commonly used international languages in the world. Therefore, learning English in schools is still becoming a priority when it comes to improving its quality. In the employment world, having English skills is a plus that is not necessarily owned by everyone, not to mention the situation in the world nowadays which is affected by globalization. This makes us realized how important the roles of English language are for the future of our students. Since the coronavirus pandemic occurred, learning activities in schools were stopped in order to minimalize the spread of the virus. They were instead changed into online activities. In online learning, teachers and students will get used to using online media, such as Zoom or Google Meet for interaction. Various forms of efforts have been made in preparation to face global competition and to adapt to the conditions at this time of pandemic. Based on the analysis of current situation and under a request from submitted by SMPN 10 Tambun Selatan, we will conduct an English language training following the needs of the students, namely Basic English Language Training. The purpose of this activity is an effort to improve the quality of human resource with the output of improving students’ English language skills and scientific publication in national journals